Cementerio de San José: historia, creencias y arte dentro de sus muros - Otárola, Flory (2013)
The History of Costa Rica has been writen within a religious and political context in which the Catholic Church has performed a starring role, not only among those living but among the dead as well. The present article offers an ilustration of it through the story of five cementeries of great historical relevance: Extranjero, General, Obrero, Calvo y Montesacro.